A comparative analysis of Engineering students' problems in speaking and writing - Sarudin, Isarji; Mohamad Ali, Afiza; Zubairi, Ainol Madziah (2009)
The objective of the study was to investigate the English language problems in terms of speaking and writing skills of engineering students at a technical university in Malaysia based on the perceptions of students and English language lecturers. The study was conducted within the framework of needs analysis as part of the larger curriculum review exercise in the effort to redesign English language courses that meet the needs of the stakeholders. A 15-item questionnaire was formulated and distributed to 612 engineering students and 36 English language lecturers of the technical university. The findings of the survey indicated that there is a difference between students’ and lecturers’ perceptions of students’ problems in speaking and writing. Based on the findings of the study relevant recommendations were made to assist in the decision making process of the curriculum review exercise.